ANALISIS PELAKSANAAN KEBIJAKAN KERJASAMA ANTAR DAERAH WILAYAH KEDUNGSEPUR BIDANG PARIWISATA - Fakhri Rahmanditya Muriawan; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Tourism Sector is a sector that assessed the potential to be developed in an effort to increase revenue for the region through tourist attraction. Kedungsepur region has a percentage of the number of tourists both from domestic and international amounted to 19.31% in 2013 and 20.34% in 2014, but its range is not evenly distributed. So that the tourism sector included in the priority scale Inter-regional Cooperation Kedungsepur area approved by the respective Regional Head in 2011. Research method uses descriptively qualitative research design with observation, interview, and literary review as the data collecting technique. The information source are Culture Division Head of Culture and Tourism Department of Semarang, Chief of Local Government and International relation of Semarang Municipality, and Destinations Section Staf Culture and Tourism Department of Central Java Province. The research result that implementation of Inter-regional Cooperation in tourism Kedungsepur region not fully accomplished, proven by the implementation of Inter-regional Cooperationin tourism Kedungsepur have found problems at every stage. When on interpretations phase, there are some issues because each area is not tourism as a major sector for each region, as well as at the application phase there are problems regarding the implementation is not accordance with the planning. Recommendation can be done to improve implemention for Inter-regional Cooperation of Kedungsepur region in tourism is need to increase the commitment of each parties that involved in cooperation, unify the understanding of each region on cooperation in tourism, also need some in-depth review of strategy to promote single destination.